Teletransporte quântico na presença de ruído - Gomes, Raphael Fortes Infante (2016)
The main focus of this work is to explore the feasibility of conducting the teleportation protocol in scenarios where the presence of an external environment reduces the purity of the input state and the transmission channel. To investigate the behavior of these protocols under realistic conditions, we selected the main decoherence maps reported in the literature concerning the description of this phenomenon, including the representation of mixed states through the Kraus operators and systems in thermal equilibrium whose Hamiltonian is described by the Heisenberg model. In this context, we proved that there are cases in which the in uence of external factors (such as increasing temperature and decoherence rates) and the immersion of those qubits in distinct environments help increasing the similarity between the properties of the original information and the teleported state. In addition, we studied the probabilistic teleportation protocol under the in uence of the same noise conditions analysed for the deterministic protocol, and the results here obtained show that the rst process can outperform the expected value of the average delity of the teleported state.